2016
DOI: 10.5539/jpl.v9n9p119
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Legal Literacy Level of the Elementary and Secondary School Teachers

Abstract: The goal of research was the comparison of legal literacy level of elementary and secondary school teachers. The research design was a descriptive-correlational method. By using stratified sampling method 158 teachers were selected and pariticipated in the study. Research tool was a researcher made questionnaire beasd on the dimentions of legal literacy. The results showed that the teachers of elementary and secondary schools have not appropriate legal literacy. The findings also indicate that there is a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…form of knowing the basic concepts of law, knowing the legal process and exercising their rights. Marzooghi et al (2016) found that primary and secondary school teachers' legal literacy levels were not adequate. Similarly, Mirabile (2013) revealed that teachers did not have sufficient knowledge about legal issues, which constitute a vital dimension of teacher-student interaction, such as student safety and student rights.…”
Section: Extended Abstractmentioning
confidence: 96%
“…form of knowing the basic concepts of law, knowing the legal process and exercising their rights. Marzooghi et al (2016) found that primary and secondary school teachers' legal literacy levels were not adequate. Similarly, Mirabile (2013) revealed that teachers did not have sufficient knowledge about legal issues, which constitute a vital dimension of teacher-student interaction, such as student safety and student rights.…”
Section: Extended Abstractmentioning
confidence: 96%
“…More than 90 % of teachers from Malasia do not have basic knowledge of education laws and believe that such a subject should become part of their vocational training (Hamid & Mohammad, 2018). Researchers from Iran suggest primary and secondary school teachers lack appropriate legal literacy too (Marzooghi, Sadeghi, Mohammadi, & Karimi, 2016). Researchers from China discuss early legal https: //doi.org/10.15405/epsbs.2020.12.74 Corresponding Author: Nadezhda V. Sivrikova Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2357-1330 566 education, law promotion among young people.…”
Section: Problem Statementmentioning
confidence: 99%